Best Practices to Achieve Optimal Geothermal Drilling Performance in A Cost-Effective Manner: Case Study of the Fastest Geothermal Well Drilling in Java and Sumatra - Bambang Yudho Suranta; Irfan Rasyid; Akhmad Sofyan; Arif Rahutama (Scientific Contributions Oil and Gas, 2023)
Indonesia, recognized for possessing substantial geothermal energy potential, is working towards harnessing the resource to achieve numerous objectives. Among the primary challenges encountered is the considerable expense of geothermal drilling. One of the most significant obstacles to achieving this objective is the high drilling cost, which constitutes 35-40% of the total cost of geothermal energy development. The drilling cost is mainly affected by the time needed to drill one well because the faster the time, the lower the cost. Therefore, this research analyzed drilling activities, identified the fastest and most effective methods for optimal geothermal drilling performance, and reduced costs. The research also determined the factors that contributed to the sustained status of Well X as the fastest well drilled in the past decade. The methodology comprised literature review, data collection through adequate background on well and geothermal field, and data analysis. The result showed that the fastest drilling operation of a geothermal well in Indonesia in 2012 occured in West Java (Well X) for only 9.9 days with 1736.5 meters (mMD). Meanwhile, in 2021, Well Y in Sumatra spent 21.74 days to reach a depth of 2200 mMD. The use of a single-run and clean-out Bottom Hole Assembly (BHA) throughout the entire section affected the drilling duration and significantly reduced the inner side cleaning time, respectively. The cost of Well Y drilling, achieved using the best performance of two wells, reduced drilling costs by 19.2%.